Women and the Law of Peoples - Martha Nussbaum (Politics Philosophy Economics 2002; 1; 283, 2002)
John Rawls argues, in The Law of Peoples, that a principle of toleration requires the international community to respect `decent hierarchical societies' that obey certain minimal human rights norms. In this article, I question that line of argument, using women's inequality as a lens. I show that Rawls's principle would require us to treat the very same practices of the very same entity differently if it happens to set up as an independent nation rather than a state within a nation, and I criticize the consequences to which this asymmetry leads. I argue that Rawls gives us no good reason to think that we cannot justify a much richer set of norms for all the world's societies. I argue, However, that issues of justification should be sharply distinguished from issues of implementation, and that respect for the moral significance of national sovereignty ought to restrain us from intervention in all but the most extreme cases.